Ut granum sinapis - Sacr (Supplementa Humanistica Lovaniensia, 1997)
In 1967 Jozef IJsewijn started the Seminarium Philologiae Humanisticae or Seminar for Neo-Latin Studies at the Katholieke Universiteit Leuven. Thanks to the founder